A dynamic model of water resources management using the scenario analysis technique in downstream of the Zayandehroud basin. Issue 4 (2nd October 2019) - Ahmadi, Azadeh; Ohab-Yazdi, Sayed Ali; Zadehvakili, Nima; Safavi, Hamid Reza
ABSTRACT: Zayandehroud River Basin has been experiencing a rapid industrial and agricultural development which caused severe water crisis with several environmental and social consequences. This study presents a dynamic model to analyse the interaction of groundwater and surface water resources in the basin by applying various conjunctive management scenarios. Different scenarios for the management of the Zayandehroud River Basin under the conjunctive use of surface and groundwater resources were evaluated. The water evaluation and planning (WEAP) and the MODFLOW models were used as the planning tool to assess the status of the basin under the designed scenarios and to simulate groundwater resources considering dynamic link between them. The proposed scenarios were based on a demand and supply management approach and accommodate changes in consumption patterns and irrigation efficiency. Finally, the designed scenarios were evaluated based on economic, social, and environmental criteria using the multi-criteria decision-making (MCDM) method. Our analysis indicated that under proper management policies the aquifer withdrawal would reduce from 74% to 62% leading to enhancement of basin sustainability.